2022
DOI: 10.3389/fphar.2022.853230
|View full text |Cite
|
Sign up to set email alerts
|

Palmatine Attenuates Metastatic Lung Colonization of Triple Negative Breast Cancer Cells

Abstract: Background: Metastatic breast cancer to the lungs is a serious, life-threatening complication that is difficult to cure. Circulating tumor cells play a key role in the metastatic spread of breast cancer to the lungs via the lymphatic or circulatory system. Palmatine is a protoberberine alkaloid, identified as an active component of traditional African herbal preparations. Palmatine has antimetastatic and antiproliferative effects. The inhibitory activity of palmatine on the metastatic colonization of triple ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…[50] At the same time, palmatine can inhibit lung metastasis of adenocarcinoma cells and prevent lung structural changes, which is achieved by upregulating the expression of tumor suppressor p53 and thus inhibiting the transcription of metastasis-associated protein 1. [51]…”
Section: Discussionmentioning
confidence: 99%
“…[50] At the same time, palmatine can inhibit lung metastasis of adenocarcinoma cells and prevent lung structural changes, which is achieved by upregulating the expression of tumor suppressor p53 and thus inhibiting the transcription of metastasis-associated protein 1. [51]…”
Section: Discussionmentioning
confidence: 99%
“…Berberine (27) sensitized the BC cells to chemotherapeutic agents via reducing XRCC1mediated base excision repair (Gao et al, 2019). Palmatine (34) reduced the lung metastasis of TNBC via downregulating metastasis-associated protein 1 (MTA1) and increasing p53 level (Ativui et al, 2022). Recently, Li Z. R. et al ( 2020) found that five protoberberine alkaloids (30-34) also showed the inhibitory activities against LSD1.…”
Section: Natural Productsmentioning
confidence: 99%
“…In studies related to its anti-cancer effect, palmatine showed considerable growth inhibition in several human cancer cell lines, such as the HepG2 human liver cancer cell line, CEM T lymphoblast cell line, K III and Lewis lung carcinoma cell lines, and MCF-7 human breast cancer cell line [ 35 , 36 ]. In addition, it exhibited an anti-proliferative effect in human ER + /HER2- breast cancer cell lines, regardless of the tumor type, and suppressed metastasis to the lungs of the 4T1 triple-negative breast cancer cell line [ 37 , 38 ]. Moreover, it induced cell death by inhibiting the PI3K/AKT pathway in human acute myeloid leukemia cell lines [ 39 ].…”
Section: Introductionmentioning
confidence: 99%